ALMA detection of the [OIII] 88 μm line in a highly-magnified Lyman break galaxy at z = 6.1. Issue Volume 15:Issue S341(2019) (November 2019) - Sunaga, Kaho; Tamura, Yoichi; Lee, Minju; Mawatari, Ken; Inoue, Akio K.; Hashimoto, Takuya; Matsuo, Hiroshi; Taniguchi, Akio
Abstract: We present a 4.7σ detection of the [OIII] 88 μ m line in a gravitationally-lensed Lyman break galaxy, RXC J2248-ID3, using the Atacama Large Millimeter/submillimeter Array (ALMA). We did not detect [CII] 158 μ m and rest-frame 90 μ m dust continuum emission, suggesting that the bulk of the interstellar medium (ISM) is ionized. Our two-component SED model combining the previous Hubble Space Telescope (HST) data and new photometry obtained from Very Large Telescope (VLT), Spitzer and ALMA suggests the presence of young (∼2 Myr) and mature (∼600 Myr) stellar components with the metallicity of Z = 0.2Z⊙ . Our findings are in contrast with previous results claiming a very young, metal-poor stellar component.